Et internationalt perspektiv på historien om jøderne i Danmark - Blüdnikow, Bent (Rambam. Tidsskrift for jødisk kultur og forskning, 2021)
The Danish Jews miraculously made it through World War II without great losses. Generally, Danish historians have sought to explain this through a national perspective, arguing that Nazis wished to continue cooperating with Danes, and that German decision makers placed in Denmark were influenced by the distinct Danish humanist approach. However, by adopting an international perspective on the Danish situation a different assessment and causality emerge. It cannot be disproven that Germans’ mild treatment of Jews in Denmark was an attempt to secure Danish export and cooperation while avoiding civil unrest, but Germans were far less kind in the rest of Europe, and there must be other explanations. Perhaps the German policy came about as a result of Heinrich Himmler and his staff’s desire to use Danish Jews as an example of Nazism’s humanity, thereby increasing Western powers’ leniency towards Germany. There is much to suggest that the 470 Danish Jews placed in Theresienstadt were to act in accordance with Himmler’s plan to give the world a positive impression of the concentration camp. It has been said that the Danish cooperation policy saved the lives of Jews in Denmark and Theresienstadt. In my opinion, however, such a conclusion is premature, and the decision to delay the rounding up of Jews in October, as well as the decision not to send Danish Jews in Theresienstadt on to Auschwitz-Birkenau, is down to other causes. It has also been suggested that Georg F. Duckwitz and Werner Best were influenced by Danish humanism and social democrats, which led them to hold back in introducing tougher measures against Danish Jews. However, I believe that this is too romantic an approach. Leading Nazis were cynical people who had contributed to brutal anti-Jewish measures and actions in other places. Their motive was to follow the strategy laid out by Himmler who propagated an unusually mild treatment of Danish Jews. This gave Nazis the chance to use the rescue of Danish Jews as a defense after the war, a successful tactic. I believe that Duckwitz was a calculating Nazi who acted out of selfishness and that his diary and later statements are problematic source material. Danish historiography has focused extensively on the rescue in 1943, an event that has justified cooperating with Germany. But the cooperating policy had a dark side: Danish export helped Germany and may have prolonged the war. Cooperation also ensured that Denmark remained calm, which enabled the Germans to move forces elsewhere, e.g. in order to persecute Jews. If we wish to weigh moral advantages and disadvantages, the international situation must be taken into consideration. Here the Danish cooperation policy had tragic repercussions.